Using the TAM and Functional Analysis to Predict the Most Used Functions of an Active Learning Classroom (ALC) - Poellhuber, Bruno; Fournier St-Laurent, Samuel; Roy, Normand (Frontiers in ICT, 2018)
Since the pedagogical reform undertaken in the field of physics teaching with the SCALE-UP project, research has shown that active learning classrooms (ALC) can lead to substantial gains. The reflection on ALC is now burgeoning, with this area being the number-one focus of university technological investments in 2017. However, even though a kind of ALC standard has emerged (teacher pod at the centre of the room, round tables, a projector for each table, etc.), very few researchers actually investigate the precise layout of ALCs and which particular features are the most important from the students’ perspective. This is precisely what this study aims to do, relying on the TAM (Technological Adoption Model). The study took place in three colleges located in Quebec which had installed an ALC using a functional analysis approach. In this process, nine functions were identified. A single-items questionnaire was developed around a modified TAM (including interest) and sent to 352 students who rated the frequency of use, utility, interest and ease of use of each of the nine functions. Qualitative data were collected through group interviews with students. Average scores were computed for each construct with the nine functions and they showed satisfactory consistency. Automated text analyses were conducted on the answers to the open-ended question. The results show that from the students’ perspective, the most important functions are related to features that facilitate group work (having a team table and using wall surfaces that can support image projections and annotations). Being able to use computers supplied by the college, connect student-owned devices to the team projector and annotate projection surfaces also ranked high. The correlation between frequency of use, interest, utility and ease of use is high and statistically significant. The qualitative data show that having comfortable, movable chairs is also important. The special look and feel of an ALC also seems to make students more comfortable. On a less positive side, some students indicate that visual obstruction is an obstacle in the periods when the teachers lecture in the class. These results may support cost-effective ALC design.